An analytical study of the role of information systems in developing medium industrial enterprises in Tartous Governorate: دراسة تحليلية لدور نظم المعلومات في تنمية المشروعات الصناعية المتوسطة في محافظة طرطوس (Journal of Hama University, 2024)
This study dealt with medium industrial project of various types in Tartous Governorate, in addition to the role of information systems, whether accounting, administrative and marketing information systems in development of this projects represented by productivity, employee income and profitability in them. In this study, the concept of information systems and their characteristics were addressed, and the nature of medium industrial projects in tartous Governorate, their reality and the difficult they faced in light of current crisis.We used the descriptive analytical approach in this study, where we studied the role of information system in the development of medium industrial projects in Tartous Governorate through a questionnaire that was distributed after ensuring its suitability for the study to the study population consisting of 150 individuals with different jobs within these projects.Several statistical methods were applied, such as the one sample – t – test and the ANOVA test. The study reached the following results:-Information systems are of great importance in the development of medium industrial projects in Tartous Governorate.-There are no statistically significant differences between the averages of the respondents, responses about the role of information systems in increasing productivity, increasing individual income, and increasing the profitability of medium industrial projects in Tartous Governorate due to the characteristics of the project.
Keywords: : information systems, medium industrial projects, development of medium industrial projects.